Opening up the notion of "closing space": accounting for normative, actor, and political system diversity. Issue 3 (3rd April 2022) - Khakee, Anna
ABSTRACT: Our understanding of the "closing space" argument is much nuanced if we widen the conceptualizations of both "closing" and "space". "Closing" would thus include state attempts to restrict not only the promotion of democratic/human rights norms, but also other types of norms (conservative, right-wing, Islamist). A broader definition of "space" would likewise include not only the space occupied by CSOs, but also that of other politically important actors, such as political parties and religious communities. Lastly, we stand to gain from putting the spotlight on democratic states' efforts to control outside influences on its domestic political sphere. The article thus proposes an analytical framework focusing on state regulations of foreign funding to CSOs, political parties, and religious communities, which is applied in two exploratory case studies of Israel and Tunisia. The article finds that the two states attempt to control norm diffusion not only via domestic CSOs, but also through political parties and religious groups. Regulations do not always target human rights and democratic norms. Foreign funding regulations have at times favoured foreign funding for nationalistic, right-wing norms: at others, democratic norms over Islamic norms. Thus, the "closing space" phenomenon is more complex than usually understood.